Pretreatment-free selective and reproducible SERS-based detection of heavy metal ions on DTPA functionalized plasmonic platform; Sensors and Actuators B: Chemical; Vol. 253 - Guselnikova O. A. Olga Andreevna; Postnikov P. S. Pavel Sergeevich; Erzina M. R. Mariya Rashidovna; Kalachyova E. Evgeniya; Svorcik V. Vaclav; Lyutakov O. Oleksy (2017, 2017)
Title screen